THE INFLUENCE OF SALES MANAGEMENT CONTROL, SALES MANAGEMENT SUPPORT AND SATISFACTION WITH MANAGER ON SALESPEOPLE’S JOB SATISFACTION (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
Salesperson's job satisfaction is of particular interest to companies because it has been linked to performance and customer retention. Contemporary sales workplace is becoming increasingly complex, but sales managers still, and more than ever, play a significant role in shaping attitudes of their salespeople. Thus, it is important to understand the influence of different sales management practices on salespeople’s satisfaction which leads to better personal and organizational results. The main aim of this paper is to explore the influence of three types of sales management control (behavior-based, knowledge-based and outcome-based control), sales management support and satisfaction with sales manager on salespeople's job satisfaction. The research was conducted among salesforce in Croatia and Italy and the data were analyzed by the PLS-SEM method. The study shows that knowledge-based control, manager support and satisfaction with manager positively impact salespeople's job satisfaction. An influence of behavior-based control and outcome-based control was not demonstrated. The findings are partly in line with previous researches, but also provide new insights into aspects of manager-seller relations. The results can help sales managers to shape the target behavior and practices, and make them aware of the importance of their role in achieving job satisfaction among their subordinates. Top and human resource (HR) managers can also hire appropriate managers that can be encouraged to implement desired practices.